1998
DOI: 10.1073/pnas.95.22.12995
|View full text |Cite
|
Sign up to set email alerts
|

δ-Tonoplast intrinsic protein defines unique plant vacuole functions

Abstract: Plant cell vacuoles may have either storage or degradative functions. Vegetative storage proteins (VSPs) are synthesized in response to wounding and to developmental switches that affect carbon and nitrogen sinks. Here we show that VSPs are stored in a unique type of vacuole that is derived from degradative central vacuoles coincident with insertion of a new tonoplast intrinsic protein (TIP), ␦-TIP, into their membranes. This finding demonstrates a tight coupling between the presence of ␦-TIP and acquisition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
117
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(120 citation statements)
references
References 31 publications
3
117
0
Order By: Relevance
“…We thus demonstrated that aquaporins are well expressed on Arabidopsis cultured cells and showed that one of the most abundant proteins present on the tonoplast is the AtTIP2.1 (Table I). Previous studies argued that plant cells have the ability to generate and maintain separate vacuole organelles with each being marked by a different TIP subtype (5,6). For example, the fully differentiated cell types PSVs are marked by ␣-TIP plus ␦-TIP, and lytic vacuoles are marked by ␥-TIP.…”
Section: Table III List Of the Abc Transporters Identified On The Tonmentioning
confidence: 99%
See 1 more Smart Citation
“…We thus demonstrated that aquaporins are well expressed on Arabidopsis cultured cells and showed that one of the most abundant proteins present on the tonoplast is the AtTIP2.1 (Table I). Previous studies argued that plant cells have the ability to generate and maintain separate vacuole organelles with each being marked by a different TIP subtype (5,6). For example, the fully differentiated cell types PSVs are marked by ␣-TIP plus ␦-TIP, and lytic vacuoles are marked by ␥-TIP.…”
Section: Table III List Of the Abc Transporters Identified On The Tonmentioning
confidence: 99%
“…PSVs contain vacuolar storage proteins to be used for anabolism during seedling growth. The function of the different vacuoles seems to be correlated with the presence of specific tonoplast intrinsic protein (TIP) isoforms (5,6). Current knowledge of the cellular traffic of higher eukaryotes indicates that vacuole biogenesis is closely related to the traffic of proteins resident in these compartments (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…This compartment fractionates distinctly from both vacuole membrane markers, ␣ -TIP and ␥ -TIP. In some plant systems, different TIP proteins mark distinct vacuoles (Paris et al, 1996;Jauh et al, 1998); however, it has not been determined whether multiple types of vacuoles are present in stigma cells. The distinct fractionation pattern for Na-PI and ␣ -TIP, however, indicates that Na-PI is unlikely to travel within "dense vesicles" similar to those that transport storage proteins in developing pea cotyledons.…”
Section: Identification Of a Prevacuolar Compartment In Stigmasmentioning
confidence: 99%
“…TIP1 subfamily is preferentially associated with the large lytic vacuoles (Jauh et al 1998). Arabidopsis thaliana AtTIP1;1 was shown to accumulate in intravacuolar invaginations made of a double tonoplast membrane (Saito et al 2002), and expression of the AtTIP1;1 is associated with cell enlargement in Arabidopsis roots, hypocotyls, leaves, and flower stems (Ludevid et al 1992), the growth-promoting hormone gibberellic acid (GA3) would up-regulated the transcriptional level of AtTIP1;1 (Phillips and Huttly 1994).…”
Section: The Transcriptional Expression Of Gjtipmentioning
confidence: 99%